2021
DOI: 10.1186/s13021-021-00195-2
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-predictor mapping of soil organic carbon in the alpine tundra: a case study for the central Ecuadorian páramo

Abstract: Background Soil organic carbon (SOC) affects essential biological, biochemical, and physical soil functions such as nutrient cycling, water retention, water distribution, and soil structure stability. The Andean páramo known as such a high carbon and water storage capacity ecosystem is a complex, heterogeneous and remote ecosystem complicating field studies to collect SOC data. Here, we propose a multi-predictor remote quantification of SOC using Random Forest Regression to map SOC stock in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The NDVI and EVI are plant indices that allow spatial estimation of soil organic matter and organic carbon and characterize vegetation information [ 54 , 55 ]. The vegetation indices can reduce the spectrum errors, and thus improve the accuracy of SOC estimation [ 56 ]. The equations used to calculate the EVI [ 50 , 57 ] and NDVI [ 50 , 58 ] are as follows (Eqs 2 and 3 ) …”
Section: Methodsmentioning
confidence: 99%
“…The NDVI and EVI are plant indices that allow spatial estimation of soil organic matter and organic carbon and characterize vegetation information [ 54 , 55 ]. The vegetation indices can reduce the spectrum errors, and thus improve the accuracy of SOC estimation [ 56 ]. The equations used to calculate the EVI [ 50 , 57 ] and NDVI [ 50 , 58 ] are as follows (Eqs 2 and 3 ) …”
Section: Methodsmentioning
confidence: 99%
“…1 ). Extended between 78º39' west longitude and 1º39' south latitude, the study area covers approximately 1667.6 km 2 (Ayala Izurieta et al 2021 ). The ecosystem boundary is the Western and Eastern Cordilleras arranged in meridian direction (Moreno et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…A database with SOC data on two soil profiles (0–30 cm and 30–60 cm) collected in 2016 and 2017 was used. The initial database contains around 500 in situ SOC sampling points, with a random spatial sampling distribution taking into account the geological units, the taxonomy of the soil, and accessibility based on the steepness of the terrain and availability of ballast roads and trails (Ayala Izurieta et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported errors in the reference citation.…”
Section: Correction To: Carbon Balance Manage (2021) 16:32 Https://doiorg/101186/s13021-021-00195-2mentioning
confidence: 99%